Radiofrequency ablation of thyroid nodules: a successful case in a public hospital in Peru: Ablación por radiofrecuencia de nódulos tiroideos; a propósito de un caso exitoso en un hospital Público en Perú. - Bedoya-Ismodes , Enrique (2024)
The results are presented, suggesting the viability of radiofrequency ablation (RFA) as an effective therapeutic strategy in the case of a 56-year-old woman with a benign thyroid nodule instead of traditional surgery at a Public Hospital in Peru. The 6-month follow-up revealed a significant reduction in the size of the nodule and a 70% reduction in volume; in addition to improved quality of life, symptom improvement, and normal thyroid function. This case highlights the evolution in the treatment of benign thyroid nodules, with RFA as a possible minimally invasive and safe option, offering a promising alternative to conventional surgical interventions for the management of thyroid nodules, marking a significant change in clinical practice. This is because it is the first hospital of the MINSA (Ministry of Health) to perform such procedures, offering multiple treatment approaches for thyroid nodules: RFA, transoral endoscopic thyroidectomy, conventional thyroidectomy, and active surveillance.